Stress and job performance among employees in Syarikat Air Melaka Berhad (SAMB) / Yuzaila Suliman and Nurshatirah Anujma Zulkifli - Suliman, Yuzaila; Zulkifli, Nurshatirah Anujma (Faculty of Administrative Science and Policy Studies, 2014)
This study is focus on the factor of stress at Syarikat Air Melaka Berhad (SAMB), which has potential to affect support level employees’ job performance. The main objective of this research is to identifying the main factor that contributes to stress towards employees’ job performance in Syarikat Air Melaka Berhad (SAMB). The research is focusing on support level employees at Syarikat Air Melaka Berhad (SAMB), which the respondents in this study consist of 99 respondents from support level employees of Syarikat Air Melaka Berhad, they were from Production Department, Operation and Consumers Department, Planning Department, Financial Department, Corporate Department and also Human Resource Department. The sampling method used is stratified sampling by disproportionate through providing questionnaire to the respondents. The theoretical framework of this study consists of dependent variable and independent variables. The dependent variable is job performance while the independent variables are workload, personal and family problem and working environment. Data collected and evidence are being processes by using Statistical Package for Social Science (SPSS) program. The analysis includes the reliability analysis, descriptive analysis, normality analysis, correlation, and regression analysis.